Productive trajectories of “agro-industrial” localities: A historical and socio-space analysis - Valinotti María, Florencia (2021)
The objective of this research work is to analyze the socio-productive trajectories of two rural towns (Córdoba, Argentina) that become agro-industrial localities from a historical and socio-space perspective. The theoretical-methodological approach favors the study of the territorial socio-economic actors that are instituted as hegemonic to account for the forms of production of space, also considering their insertion in macro-national and global processes. The study extends throughout the 20th century to the present and is systematized based on the different territorial pacts that were formed. The conclusions make it possible to identify the internal structure of the agents that make up the dominant sector at the territorial level and their role in defining the productive profile of the localities.